Women, Climate Resilience, and Rural Life: A Case Study of Agryouli Village - Sabitri Lamichhane, (Journal of Development Review, 2025)
Climate change, increasingly recognized as a human-induced phenomenon, is transforming both ecological systems and rural socio-cultural structures. This study investigates the gendered dimensions of climate change in Agryouli village, located in Nepal’s Terai region. Women, despite their marginal role in household and community decision-making, are disproportionately affected due to their close dependence on natural resources for food preparation, fuel collection, and subsistence farming. Drawing on traditional ecological knowledge, women interpret environmental cues to guide agricultural activities. However, their adaptive capacity remains limited by unequal access to income, land, and institutional resources. Based on 25 years of longitudinal fieldwork, the study identifies significant environmental changes particularly in rainfall patterns, crop cycles, and water availability as key stressors. Rather than detailing specific livelihood shifts, the abstract highlights how these disruptions have deepened socio-economic inequality and increased burdens on women and girls. Despite these challenges, emerging cooperative practices suggest a path toward local resilience. The findings call for inclusive, gender-responsive adaptation strategies that address structural inequalities and promote long-term sustainability.